The effects of grain texture and phenotypic traits on the thin-layer drying rate in maize (Zea mays L.) inbred lines - Le-xiu SUN; Shuang-xi LIU; Jin-xing WANG; Cheng-lai WU; Yan LI; Chun-qing ZHANG (Journal of Integrative Agriculture, 2016)
Abstract: To explore the relation of maize grain texture and phenotypic traits with grain thin-layer drying rate, we observed the ultra-structure of maize grain, and tested three traits about the maize grain texture and four phenotypic traits. The vitreous part percentage was different (P<0.05) among different maize inbred lines. There was a significant relationship between the drying rate with grain texture and phenotypic traits. Main factors that influenced the drying rate were different during different drying stages. New results observed that empirical constants (k and N) in drying equation were different for seed of the 30 inbred lines of maize. The k of simplified diffusion equation and N of page equation were significantly influenced by both grain texture and phenotypic traits. These results could be used as guideline parameters for drying maize seeds having different grain characteristics during different drying stages.